PARTISIPASI ANGGOTA MENGIKUTI PROGRAM PKK (PEMBINAAN KESEJAHTERAAN KELUARGA) DI RT 01-04 RW 7 KELURAHAN SIALANG MUNGGU KECAMATAN TAMPAN KOTA PEKANBARU - Riya Amelia Mazli; Aswandi Bahar; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine Participation of Members Following PKK Program (Family Welfare Development) In RT 01-04 RW 7 Sialang Munggu Village Tampan District Pekanbaru City. The formulation of the problem in this study is how high Participation of Members Follow PKK (Family Welfare Development) In RT 01-04 RW 7 Sialang Munggu Subdistrict Tampan City Pekanbaru District.The type of this research is descriptive with quantitative approach. The population in this study were PKK members in Sialang Munggu sub-district Tampan Kota Pekanbaru City all members of population 100 people. Technique of sampling using Random Sampling Technique, which is taken at random according to PKK member, hence obtained sample amounted to 50 people. The data collecting technique in this research is questionnaire technique, amounting to 93 items statement about Member Participation Following PKK Program (Family Welfare Development) in RT 01-04 RW 7 Sialang Munggu Village Tampan Sub-district Pekanbaru City, with indicator Idea / idea, Power, and The material consists of 10 sub indicators that are divided into 16 dimensions. Data obtained from the respondents who numbered 20 people for the sample trial, there are 11 items are invalid, so the whole instrument declared realibel with alpha crobach = 0.98. Based on the results of data analysts showed that Participation of Members Following PKK Program (Family Welfare Development) In RT 01-04 RW 7 Sialang Munggu Kecamatan Tampan Kota Pekanbaru in review of Idea / idea, classified Very high with percentage 95.44%, then reviewed from Power also classified Very High with 100.37% percentage, then in the review of the material also classified as Very High 94.7%. While the most dominant Participation is Ideas / ideas, this is based on the assessment criteria in the set, it can be concluded that the Participation of Members Following PKK Program (Family Welfare Development) In RT 01-04 RW 7 Sialang Munggu Village Tampan District Pekanbaru City in review the whole of each dimension in view of the average score, is quite high. Meaning Participation of Members Following PKK Program (Family Welfare Development) In RT 01-04 RW 7 Sialang Munggu Kecamatan Tampan Pekanbaru City has been implemented optimally with a percentage that indicates high criteria.Keywords: Participation, PKK